The gross motor skills of children with mild learning disabilities - Nonis, Karen; Tan, T. (International Journal of Special Education, 2014)
Many international studies have examined the gross motor skills of children studying in special schools while local studies of such nature are limited. This study investigated the gross motor skills of children with Mild Learning Disabilities (MLD; n = 14, M age = 8.93 years, SD = .33) with the Test of Gross Motor Development-2 (TGMD-2, Ulrich, 2000). The TGMD-2 consists of 12 items equally divided into two subtests (locomotor and object control). The locomotor subtest includes run, gallop, hop, leap, horizontal jump and slide while the object control subtest includes strike a stationary ball, stationary dribble, kick, catch, overhand throw and underhand roll. The results revealed significant differences in 8 out of 12 test items: gallop, hop, leap, horizontal jump, slide, strike, dribble and roll at mastery level between children with MLD and TGMD-2 norm population. The authors suggest motor interventions for children with MLD to improve their gross motor skills.